Bladder Stone 6 Years after Intravaginal Slingplasty: A Case Report and Review of Literature - Fulya Dökmeci; Şerife Esra Çetinkaya; Vugar Bayramov; Kaan Aydos (Gynecology Obstetrics & Reproductive Medicine)
We present a 42 year-old patient with a history of intravaginal slingplasty operation performed 6 years ago admitted with persistent lower urinary tract symptoms, dyspareunia and chronic pelvic pain for almost four years. She had undergone two previous cyctoscopies in which only mucosal edema had been reported. After a detailed urogynecological examination, a bladder stone over a mesh at the bladder neck was revealed at her third cystoscopy and was removed. Persistent urogenital symptoms should remind the possibility of unrecognized, intraoperative transvesical passage of the mesh or mesh erosion and stone formation over it even after years and even in the presence of a normal postoperative cystoscopy; a thorough cystoscopic evaluation, particularly paying attention at the urethra and bladder neck, should be performed in any case with a history of sling procedures.